Management Accounting Reports Supporting Executive Performance Evaluation (gjstudies, 2025)
This research introduces a novel, cross-disciplinary framework for executive performance evaluation by integrating principles from computational linguistics, networktheory, and behavioral economics into traditional management accounting report structures. Moving beyond conventional financial metrics and balanced scorecards, we propose the Dynamic Semantic Performance Evaluation (DSPE) model, which analyzesthe qualitative narratives within management accounting reports—such as managerialcommentary, risk assessments, and strategic initiative descriptions—to extract latentperformance signals. The methodology employs a hybrid approach combining semanticrole labeling adapted from natural language processing, sentiment trajectory analysis,and coherence network mapping to quantify executive strategic thinking, communication clarity, and alignment with organizational objectives. We developed a proprietary corpus of 150 anonymized management reports from diverse industries spanning1998-2004 and applied the DSPE model to evaluate the reports’ supporting role inperformance assessment. Results demonstrate that DSPE-derived metrics, particularly ’strategic coherence density’ and ’narrative foresight alignment,’ provide significant explanatory power for subsequent organizational outcomes, explaining 42% ofthe variance in long-term firm adaptability measures, a substantial improvement overtraditional variance analysis (15%). The model successfully identified high-performingexecutives who were overlooked by purely quantitative metrics and flagged potentialstrategic myopia in cases where financials appeared strong. This research contributesoriginality by fundamentally re-conceptualizing management accounting reports not aspassive repositories of financial data but as active, structured narratives that encodeexecutive cognitive patterns and strategic capability. It offers a novel methodologicalbridge between accounting practice and computational text analysis, providing a moreholistic, dynamic, and forward-looking tool for governance and evaluation.